Development of TPACK-Based Electronic Magazine Physics Teaching Materials to Enhance Technology Literacy of High School Students - Fitriyawany; Ida Meutiawati; Alfina Citrasukmawati; Fauriza Hafni (Didaktika: Jurnal Kependidikan, 2024)
This study aims to design Physics teaching materials in the form of an electronic magazine based on TPACK to enhance technological literacy among high school students (SMA/MA) in Banda Aceh. The materials are intended to be feasible, valid, and practical. The study employs Research & Development methodology using the Alessi and Trollip development model. The subjects of the electronic magazine trial were 30 eleventh-grade students from SMA/MA in Banda Aceh. The feasibility assessment instrument for the electronic magazine was validated by six media expert validators and six content expert validators. The practicality assessment instruments consisted of teacher response questionnaires and student response questionnaires. This development research was completed through several stages of product revision, ensuring that the developed magazine is valid and practical for use in teaching. The feasibility of the electronic magazine was determined to be in the "very feasible" category, based on an average score of 4.42 or 88.56% from the media expert validators, and an average score of 4.41 or 88.27% from the content expert validators. This is supported by the results of the teacher response analysis, which was very positive with a score of 90.56%, and further confirmed by an average positive student response score of 87.35%. This indicates that the development of the Physics teaching materials in the form of an electronic magazine based on TPACK to improve technological literacy among high school students in Banda Aceh is feasible and practical for use in teaching.